LOST TO FOLLOW UP BEHAVIOUR WITH COMPLIANCE BEHAVIORIN HIV/AIDS PATIENTS IN THE SPECIAL REGION OF YOGYAKARTA - Ahmad Zulfan Khanafi; Lilis Setiyaningsih; Anis Sartika; Mahfidhoh; Nessy Anggun Primasari (Universitas Karya Husada Semarang, 2024)
The implementation of ARV therapy is one of the keys to the success of HIV/AIDS treatment programs aimed at preventing the spread of HIV infection and improving the quality of life of People Living With HIV/AIDS (PLWHA). Knowing the relationship between lost to follow up and adherence to ARV therapy in HIV/AIDS patients in the Special Region of Yogyakarta. This type of quantitative research with a cross-sectional research design. This research was carried out at the Victory Plus Yogyakarta Foundation from April to August 2024. The respondents in this study were PLWHA aged 17-50 years infected with HIV in 2023 with the assistance of the Victory Plus Yogyakarta Foundation totaling 124 people. The research instruments used were the Health Belief Model lost to follow up and MMAS-8 (Morisky Medication Adherence Scale). Analysis uses the gamma correlation test. The majority of respondents had less lost to follow up behavior, 66 respondents (52.8%). 100 respondents (80.0%) had ARV therapy adherence among respondents who were non-compliant with ARV therapy. The statistical test results showed that the p value was <0.000, which was smaller than 0.05, so there was a relationship between lost to follow up behavior and adherence to ARV therapy in HIV/AIDS patients in D.I Yogyakarta. Based on this research, lost to follow up plays an important role in adherence to ARV consumption.